1992
DOI: 10.1159/000261435
|View full text |Cite
|
Sign up to set email alerts
|

An in vitro Assessment of the Extent of Caries under Small Occlusal Cavities

Abstract: Many clinicians take for granted that occlusal caries which is just visible as a cavity is extended (deep) into the dentine. This study was aimed at quantifying this opinion. The study was carried out with 60 molars containing small but visible occlusal cavities. After taking bite-wing radiographs the crowns were separated from the roots and embedded. 700-μm sections were cut and glued on plastic sheets. X-ray pictures were taken of the sections which were scored by independent examiners. The bite-wings provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0
1

Year Published

1992
1992
2018
2018

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(12 citation statements)
references
References 1 publication
0
11
0
1
Order By: Relevance
“…It is known that the histological examination is the gold standard to assess the extent to which a tissue is affected by disease [Mitropoulos et al, 2010]; however, it is not an available tool in clinical practice. On the other hand, radiographic examination is the method of choice to assess caries depth [van Amerongen et al, 1992;Ekstrand et al, 1997]. In the present in vivo study, a sample of 95 teeth with dark shadow from dentin was assessed, and 85.3% did not present a radiolucent image (67.4%) or presented a radiolucent image restricted to the enamel-dentin junction (17.9%).…”
Section: Discussionmentioning
confidence: 92%
“…It is known that the histological examination is the gold standard to assess the extent to which a tissue is affected by disease [Mitropoulos et al, 2010]; however, it is not an available tool in clinical practice. On the other hand, radiographic examination is the method of choice to assess caries depth [van Amerongen et al, 1992;Ekstrand et al, 1997]. In the present in vivo study, a sample of 95 teeth with dark shadow from dentin was assessed, and 85.3% did not present a radiolucent image (67.4%) or presented a radiolucent image restricted to the enamel-dentin junction (17.9%).…”
Section: Discussionmentioning
confidence: 92%
“…Laboratory work, in which the validity of radiographic decisions were checked histologically, showed that false positives are uncommon [Ricketts, 1991;Russell and Pitts, 1991;Tveit et al, 1991]. On the other hand, it has been re ported that radiographs considerably underestimate le sion size [Ricketts, 1991;van Amerongen et al, 1992], It is possible that demineralisation presents relatively late on radiographs because the rays pass through intact buccal and lingual enamel as well as dentine, and the scatter from soft tissues affects contrast. A clinical trial in which the validity of the radiographic diagnosis is checked by oper ative intervention seems overdue.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, radiographs have been shown to underestimate the size of the lesion considerably. 10 Digitally enhanced radiography was developed to improve the use of radiograph for diagnosis of early caries. Using computer technology to enhance images from a video camera or from a digital x-ray sensor has been proven to be an objective and reproducible methodology.…”
Section: Introductionmentioning
confidence: 99%